1994
DOI: 10.1111/j.1740-8261.1994.tb00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal Variation in Size of the Lateral Ventricles of the Labrador Retriever Dog as Assessed by Magnetic Resonance Imaging

Abstract: Detecting canine brain lesions on computed tomography (CT) or magnetic resonance (MR) scans can be difficult if the lesions do not enhance well following administration of intravenous contrast material. Changes in the shape and position of the ventricular system can be important in the diagnosis of such lesions. Normal variation within the canine ventricular system has not been documented. MR scans from 62 normal Labrador retriever type dogs were evaluated. Five dogs had symmetric enlargement of the ventricles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 11 publications
1
30
0
4
Order By: Relevance
“…Inducing a brain adaptation to the vault architecture required compression in the dorsoventral axis, thus increasing the difficulty of identifying different brain regional structures. According to Schroeder et al, [36] brachycephalic breeds have larger LVVs than dolichocephalic and mesocephalic breeds [36][37][38][39][40][41]. Based on our results, age appears to influence the LVV in a statistically significant way, which Sue et al also found [42].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Inducing a brain adaptation to the vault architecture required compression in the dorsoventral axis, thus increasing the difficulty of identifying different brain regional structures. According to Schroeder et al, [36] brachycephalic breeds have larger LVVs than dolichocephalic and mesocephalic breeds [36][37][38][39][40][41]. Based on our results, age appears to influence the LVV in a statistically significant way, which Sue et al also found [42].…”
Section: Discussionsupporting
confidence: 65%
“…However, asymmetries between both LVVs were found, with the left lateral ventricle always larger than the right lateral ventricle. The asymmetry of the lateral ventricles is considered normal in healthy dogs up to a certain value [36,37,39,48,49]. In a study using Labrador retrievers, De Haan et al [37] estimated an asymmetry of 31%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high prevalence of congenital and acquired hydrocephalus in beagles may affect these results (Cammermeyer, 1961). Asymmetry of the lateral ventricles was studied in male Labrador Retrievers (n = 62; BW = 35-50 kg) of unknown age using MRI (DeHaan et al, 1994). In this study only 39% of the subjects were found to have asymmetric lateral ventricles, without specifying which side was larger.…”
Section: Resultsmentioning
confidence: 88%
“…Asymmetry of the lateral ventricles was studied in different breeds (Labrador Retrievers, DeHaan et al, 1994;English Bulldogs, Ryan et al, 2014). However, the classification of symmetry was based on the subjective observation of MRI images; therefore slight levels of asymmetry may have been evaluated inaccurately.…”
mentioning
confidence: 99%